Basic Theoretical Notions of Cognitive Linguistics and Their Possible Applications - Žic Fuchs, Milena (Array, 2014)
This keynote lecture addresses how basic theoretical notions of Cognitive Linguistics can be applied and implemented in language teaching and language acquisition. Special emphasis is put on vocabulary structure organized around the basic notion of prototype and directly connected to the basic notion of cognitive economy. The present perfect, a very difficult grammatical structure for non-native speakers of English, is shown on the basis of construction grammar to be by far easier to acquire for non-native speakers. The necessity of bridging the gap between theory and practice was stressed.